Peacemaking from above, peace from below ending conflict between regional rivals - Ripsman, Norrin M. (Cornell studies in security affairs, 2016)
This work explains how regional rivals make peace and how outside actors can encourage regional peacemaking. Through a qualitative empirical analysis of all the regional rivalries that terminated in peace treaties in the twentieth century - including detailed case studies of the Franco-German, Egyptian-Israeli, and Israeli-Jordanian peace settlements - the text concludes that efforts to encourage peacemaking that focus on changing the attitudes of the rival societies or democratizing the rival polities to enable societal input into security policy are unlikely to achieve peace